Bio-related applications of porous organic frameworks (POFs). Issue 15 (19th March 2019) - Zhang, He; Li, Guoliang; Liao, Chunyang; Cai, Yaqi; Jiang, Guibin
Abstract : Porous organic frameworks (POFs) are promising candidates for bio-related applications. This review highlights the recent progress in POF-based bioapplications, including drug delivery, bioimaging, biosensing, therapeutics, and artificial shells. These encouraging performances suggest that POFs used for bioapplications deserve more attention in the future. Abstract : Increasing attention has been given to the field of porous organic frameworks (POFs) due to their unique properties, outstanding performance, and broad applications. Given their extremely high surface area, ordered crystal structure, and ease of tailoring, POFs are promising candidates for gas adsorption and separation, catalysis, supercapacitors, chemosensors, and bio-related applications. Furthermore, their tunable pore size and high agent loading capacity make them promising candidates for drug delivery, whereas their ease of functionalization leads to target specificity and long blood circulation times, which are important properties in bioimaging. For biosensing applications, the pores and channels of POFs can accommodate target molecules and induce specific recognition. POFs can also be applied in phototherapy in combination with photosensitizers. Finally, POF-based artificial shells can encapsulate bioactive molecules and strengthen the resistance of cells to adverse environmental conditions. In this review, we will highlight the research progress of POF-based bio-related applications, including drug delivery, bioimaging, biosensing agents, as well as in phototherapy and artificial shells. Furthermore, the in vitro and in vivo toxicological studies of POFs are discussed as are the prospects and future research directions for POFs in bio-related applications.